Physicochemical Properties of Soil Contaminated With Refined Petroleum Oil In Eluama Community, Abia State, Nigeria - F.U., Ike-Amadi2 , C. A. and Agomoh1 , N, Ezeigbo1 , O. R., Ukpabi C. F., Abel-Anyebe3 , O., Okike-Osisiog (International Journal of Scientific Research and Management (IJSRM), 2013)
The physicochemical properties of soil polluted with refined petroleum was carried outbetween January and May, 2012, in Eluama community polluted with refined petroleumwas carried out between January and May, 2012, in Eluama community, Abia State ,Nigeria. The aim of this study is to examine the long-term kinetics of refined petroleum oilcontaminated soil and to assess the extent of remediation with respect to length of timewith the spill (11 years of spill). The soil physicochemical properties were evaluated usingdifferent analytical methods. Soil collected from unpolluted farmland was used as control.The results revealed that organic carbon, organic matter, calcium and magnesiumincreased with increase in pollution while nitrogen, potassium, sodium and phosphorusdecreased with increase in pollution. The pH became more basic as pollution decreases. Inaddition, concentration of heavy metals increased as soil increases with pollution. Thisresult reveals that the polluted soil when compared with the control (soil from unpollutedfarmland) is unsuitable for agricultural activities as full remediation has not taken placeexcept remediation can be hastened.